Stated preferences for improved air quality management in the city of Nairobi, Kenya - Ndambiri, Hilary; Mungatana, Eric; Brouwer, Roy (The European Journal of Applied Economics, 2015)
The study uses contingent valuation (CV) framework to assess individuals’ preferences for improved air quality management through motorized emission reductions in the city of Nairobi, Kenya. A conventional payment card (PC) is used to draw preferences from individuals in order to estimate the mean and the median willingness to pay (WTP) for air quality improvements in the city. Through interval regression analysis, the study finds that individuals are, on average, willing to pay Kshs. 396.57 (4.67) and a median of Kshs. 244.94 (2.88) to improve air quality management in the city. These amounts are found to increase with male gender, individuals’ income, certainty about future income and residence in an urban area. These amounts, however, decline with age, residential distance from nearby roads, and motor vehicle ownership. On the whole, the study shows significant public support towards improved air quality management in the city, which is of vital importance for effective formation and implementation of air quality management programmes.